2014
DOI: 10.2337/dc14-0030
|View full text |Cite
|
Sign up to set email alerts
|

Recovery of Hypoglycemia Awareness in Long-standing Type 1 Diabetes: A Multicenter 2 × 2 Factorial Randomized Controlled Trial Comparing Insulin Pump With Multiple Daily Injections and Continuous With Conventional Glucose Self-monitoring (HypoCOMPaSS)

Abstract: OBJECTIVETo determine whether impaired awareness of hypoglycemia (IAH) can be improved and severe hypoglycemia (SH) prevented in type 1 diabetes, we compared an insulin pump (continuous subcutaneous insulin infusion [CSII]) with multiple daily injections (MDIs) and adjuvant real-time continuous glucose monitoring (RT) with conventional self-monitoring of blood glucose (SMBG). RESEARCH DESIGN AND METHODSA 24-week 2 3 2 factorial randomized controlled trial in adults with type 1 diabetes and IAH was conducted. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

14
208
0
12

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 199 publications
(236 citation statements)
references
References 37 publications
14
208
0
12
Order By: Relevance
“…The lack of improvement in Gold score with CGM is consistent with findings seen in the IN CONTROL study 15 and in a retrospective audit 19. The HypoCOMPaSS study showed that restoration of hypoglycaemia awareness can be achieved, but that self‐monitoring capillary blood glucose and CGM have an equivalent effect on impaired awareness of hypoglycaemia 20. However, the study designs and technologies implemented differ, and further research is warranted to explore the impacts of technology as an adjunct to education in people with Type 1 diabetes and impaired awareness of hypoglycaemia.…”
Section: Discussionsupporting
confidence: 83%
“…The lack of improvement in Gold score with CGM is consistent with findings seen in the IN CONTROL study 15 and in a retrospective audit 19. The HypoCOMPaSS study showed that restoration of hypoglycaemia awareness can be achieved, but that self‐monitoring capillary blood glucose and CGM have an equivalent effect on impaired awareness of hypoglycaemia 20. However, the study designs and technologies implemented differ, and further research is warranted to explore the impacts of technology as an adjunct to education in people with Type 1 diabetes and impaired awareness of hypoglycaemia.…”
Section: Discussionsupporting
confidence: 83%
“…CGM was not associated with an improvement in IAH or SH in this study. 38 Wong et al, assessed CGM use in the T1D exchange registry. Of the 1662 participants reporting CGM use at enrollment into the registry, 675 (41%) reported discontinuing CGM after 1 year.…”
Section: Adherencementioning
confidence: 99%
“…Uninterrupted RT-CGM was advocated in our trial (3), but only 17% achieved .80% sensor usage (2), which provides evidence of likely real-world use with this iteration of the technology in unselected adults with IAH. This is in contrast to published efficacy studies, where those with SH have typically been excluded and only those prepared to wear sensors for the majority of the time were allowed to participate (5)d precluding extrapolation to real-world practice.…”
mentioning
confidence: 99%
“…We do not agree that education, weekly telephone contact, and monthly visits (as part of a targeted 6-month intervention for those with impaired awareness of hypoglycemia [IAH]) should be dismissed as unachievable. We have shown the potential for a .10-fold reduction in severe hypoglycemia (SH)dincluding in those patients not receiving more costly technological interventions (2). Moreover, given increasing availability of bolus calculators on both handheld glucometers and cell phone apps, there is no reason why access should be limited to those using continuous subcutaneous insulin infusion (CSII) or real-time continuous glucose monitoring (RT-CGM).…”
mentioning
confidence: 99%